3D Microfluidic Bone Tumor Microenvironment Comprised of Hydroxyapatite/Fibrin Composite - Ahn, Jungho; Lim, Jungeun; Jusoh, Norhana; Lee, Jungseub; Park, Tae-Eun; Kim, YongTae; Kim, Jangho; Jeon, Noo Li (Frontiers in Bioengineering and Biotechnology, 2019)
Bone is one of the most common sites of cancer metastasis, as its fertile microenvironment attracts tumor cells. The unique mechanical properties of bone extracellular matrix (ECM), mainly composed of hydroxyapatite (HA) affect a number of cellular responses in the tumor microenvironment (TME) such as proliferation, migration, viability, and morphology, as well as angiogenic activity, which is related to bone metastasis. In this study, we engineered a bone-mimetic microenvironment to investigate the interactions between the TME and HA using a microfluidic platform designed for culturing tumor cells in 3D bone-mimetic composite of HA and fibrin. We developed a bone metastasis TME model from colorectal cancer (SW620) and gastric cancer (MKN74) cells, which has very poor prognosis but rarely been investigated. The microfluidic platform enabled straightforward formation of 3D TME composed the hydrogel and multiple cell types. This facilitated monitoring of the effect of HA concentration and culture time on the TME. In 3D bone mimicking culture, we found that HA rich microenvironment affects cell viability, proliferation and cancer cell cytoplasmic volume in a manner dependent on the different metastatic cancer cell types and culture duration indicating the spatial heterogeneity (different origin of metastatic cancer) and temporal heterogeneity (growth time of cancer) of TME. We also found that both SW620 and MKN72 cells exhibited significantly reduced migration at higher HA concentration in our platform indicating inhibitory effect of HA in both cancer cells migration. Next, we quantitatively analyzed angiogenic sprouts induced by paracrine factors that secreted by TME and showed paracrine signals from tumor and stromal cell with a high HA concentration resulted in the formation of fewer sprouts. Finally we reconstituted vascularized TME allowing direct interaction between angiogenic sprouts and tumor-stroma microspheroids in a bone-mimicking microenvironment composing a tunable HA/fibrin composite. Our multifarious approach could be applied to drug screening and mechanistic studies of the metastasis, growth, and progression of bone tumors.